Interaction of Various Generic Forms in the 12th–17th Century Texts and the Mindsets of Old Russian Authors - Anatoly S. Demin (Studia Litterarum)
The essay focuses on the understudied question of the poetics of Old Russian literature: it is the first study of the kind that analyzes semantic interaction of different generic forms in the works of the period. The essay is comprised of five section each devoted to a specific work. The first section examines historical narrative in its relation to sermons, eulogies, and biblical excerpts in The Tale of Bygone Years (the beginning of the twelfth century) and comes to the conclusion that the chronicler was not content with the negligence of his listeners and readers. The second section examines the interrelation of factual material and sermon in Novgorodskaa First Chronicle (the thirteenth and fourteenth centuries) and reveals the chronicler’s severe attitude towards his contemporaries. The third section examines a series of two works by Moscow Dyak Rodion Kozhuh as part of Sofiyskaya Second Chronicle and shows the author’s personal inclination to the expressiveness of style. The fourth section examines a combination of prosaic and rhymed fragments from the Saying of Avraamy Palitsyn written in the 1620s and comes to the conclusion that the author was inclined to philosophically reflect on the Time of Troubles. Finally, the fifth section examines a combination of the rhymed narrative with poetical sermons in The Story of Unfortunate Misfortune (1660s) and shows the author’s pessimistic mindset. The essay ends with a very tentative conclusion: the interaction of different generic forms of narration was typical for the whole оf Оld Russian literature. The variety of purposes and mindsets prompted authors to employ various generic types of narration.